Penyajian Data Dalam Bentuk Diagram dan Tabel - Hanifah, Ummu; Fakhira, Dhea; Panggabean, Hadi Saputra (CV. Rayyan Dwi Bharata, 2025)
Effective data presentation is an important element in statistical analysis, especially in education and research. This article discusses the importance of effective data presentation through diagrams and tables in statistical analysis, particularly in education and research. By using diagrams, such as bar and pie charts, complex information can be visualized in an attractive way, making it easier to understand trends and comparisons between categories. Meanwhile, tables provide an organized structure for presenting numbers and categories, which is very useful for the analysis and comparison of numerical data. This research uses the literature study method to collect and analyze information from various academic sources, showing that the selection of appropriate presentation methods can enhance readers' understanding and strengthen the credibility of information.